Effect of stratification and scarification with gibberellic acid on germination of seeds of the apple variety "Golden Delicious" - مخول جرجس; رباب ديوب (Latakia University Journal -Biological Sciences Series, 2023)
The research was carried out 2020 and 2021 at the nursery of Tishreen University and the laboratories of the Faculty of Agriculture to study the effect of stratification and soaking with gibberellic acid, on extracting the embryos of seeds of the "Golden delicious" cultivar from their dormancy phase, and on increasing their germination rate. The results showed the following: *The wet cold stratification at a temperature of (5 ± 2 C) for 60 days after soaking in a solution of gibberellic acid at a concentration of 250 and 500 ppm for 24 hours led to an increase in the percentage of germination of seeds of the apple variety “Golden Delicious” from 7.78% in the control seeds to 94.45% and 92.23%, respectively, as an average for the two years of study, with no significant difference between them. The stratification treatment for 60 days before planting and the stratification treatment for 45 days after soaking with gibberellic acid at a concentration of 500 ppm for 24 hours gave a germination rate of 86.67% for each, followed by the stratification treatment for 90 days with a germination rate of 83.33% without a significant difference between these treatments. * Wet cold stratification treatment at a temperature of (5 ± 2 °C) for 60 days after soaking in gibberellic acid solution at a concentration of 250 ppm for 24 hours outperformed significantly the other of the treatments except of soaking treatment at a concentration of 500 ppm and then stratification for 60 days before planting.